Anglicyzmy jako komponenty frazeologizmów w rosyjskim języku młodzieżowym . - Kubecka, Katarzyna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article is devoted to English borrowings as components of idioms in Russian youth slang. English borrowings are treated by young Russian language users as ‘a base’ for various combinations of English and Russian words in creating various creative neologisms and innovative modifications of existing idioms in Russian. The variations are aimed at emotions and humour – the essentials elements of youth slang. The use of English borrowings in Russian idioms also show their complete assimilation in the recipient language.